Elimu, educación es vida (Journal of Parents and Teachers, 2014)
The article describes the launching of the Elimu education campaign within the framework of the Ayuda en Acción organization. The objectives of the initiative are to raise awareness of the importance of education as a tool to eradicate poverty. The article also includes a synopsis of the winning story of the competition organized by Ayuda en Acción to mark its launch. The article also presents an interview with the author in which the objectives and work axes of the project are perceived.
Keywords: Project, rights, education, awareness